2012
DOI: 10.1016/s2255-4971(15)30016-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 2-Butyl-Cyanoacrylate Adhesive in Osteotomies and Bone Grafts in Rabbits: Macroscopic and Radiographic Characteristics

Abstract: Objective: To evaluate the effect of butyl-2-cyanoacrylate tissue adhesive in osteotomies and bone grafts, with regard to macroscopic and radiographic characteristics. Methods: Forty-eight rabbits were used, randomly divided into four groups of 12 animals, with observation periods of two, four, eight and 16 weeks. Both thoracic limbs were operated in each animal and two osteotomies were performed in each of the radii, withdrawing a bone fragment (bone graft) of 1 cm in length. On one side, the bone graft was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Different types of cyanoacrylate adhesives are employed in various surgical fields, including orthopedics (e.g., Foresta et al, ; Xavier & Leite, ) and oral surgery to close the wounds after apico‐ectomies, molars extractions, and mucogingival grafting (e.g., Pérez, Fernández, Márquez, & Bretaña, ). Cyanoacrylates were used with positive results in experimental studies in rabbits (Salata et al, ; Xavier & Leite, ). However, other experimental studies reported better outcomes at grafts secured with screws compared to grafts secured with cyanoacrylate adhesive (Baş et al, ; Caneva et al, ; De Santis, Silva, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of cyanoacrylate adhesives are employed in various surgical fields, including orthopedics (e.g., Foresta et al, ; Xavier & Leite, ) and oral surgery to close the wounds after apico‐ectomies, molars extractions, and mucogingival grafting (e.g., Pérez, Fernández, Márquez, & Bretaña, ). Cyanoacrylates were used with positive results in experimental studies in rabbits (Salata et al, ; Xavier & Leite, ). However, other experimental studies reported better outcomes at grafts secured with screws compared to grafts secured with cyanoacrylate adhesive (Baş et al, ; Caneva et al, ; De Santis, Silva, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The cyanoacrylate adhesive, such as the methyl 2-cyanoacrylate or the ethyl 2-cyanoacrylate, showed a good biomechanical strength for fixation of grafts (Vieira et al, 2016) and have been shown in vitro to be biocompatible (De Melo et al, 2013). Different types of cyanoacrylate adhesives are employed in various surgical fields, including orthopedics (e.g., Foresta et al, 2015;Xavier & Leite, 2015) and oral surgery to close the wounds after apico-ectomies, molars extractions, and mucogingival grafting (e.g., Pérez, Fernández, Márquez, & Bretaña, 2000). Cyanoacrylates were used with positive results in experimental studies in rabbits (Salata et al, 2014;Xavier & Leite, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All specimens assessed presented adhesive residue; however, in the butyl-2-cyanoacrylate group, these residues were larger in diameter. In fact, the rapid polymerization of that adhesive may originate solid nodules that act as true “foreign bodies.” These remain attached to bone tissue and adjacent musculature, perpetuating a white cell line at high levels 17 ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The medical literature leaves no doubt as to the safety and efficacy of the use of these adhesives. However, there are few reports 14 , 15 , 16 , 17 on their use in the treatment of bone lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The shear strength of the device was significantly higher in the absence of adhesive (43.98 N at 30 days, and 78.55 N at 60 days), compared with the adhesive group. The lower average values observed in the adhesive group may be related to the cyanoacrylate not being metabolized, 17 thereby hindering the interlocking of newly formed bone with the titanium device 18 …”
Section: Discussionmentioning
confidence: 99%